Sustainable commons governance and climate justice: ecofeminist insights and indigenous traditions - Perkins, Patricia E., author (Colorado State University. Libraries, 2017)
This paper brings together North American and global examples of traditional and new forms of "commons" which help to meet local subsistence needs and develop communities' social, political and economic resilience in the face of climate change. Commons governance represents a dynamic means of risk reduction which addresses the shortcomings of both market and state-oriented governance and is becoming increasingly relevant as climate change threatens human subsistence worldwide. Indigenous traditions and leadership are central to this (re-)emergent phenomenon. Drawing on the literatures of ecological economics, political ecology, and ecofeminism as well as the work of Elinor Ostrom to situate these ideas, this paper sets out a framework for assessing communities' climate resilience from an equity standpoint, in terms of their commons-readiness. Some of the indicators involved in this framework include each community's openness/boundaries, historical experiences and aptitudes with commons, indigenous leaders and integration of indigenous culture, social networks and social learning, political and economic autonomy, income distribution, and women's empowerment. Climate justice -- improving the local and global equity of climate change impacts and procedures – advances in parallel with commons development; this paper also discusses scale issues related to local, regional, watershed-based, international and global commons and climate justice.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: climate justice; community resilience; commons; community development; climate risk reduction; extreme weather events; social capital; participatory governance; ecological economics; political ecology; ecofeminism; indigenous governance; social learning; subsistence